2014
DOI: 10.1016/j.immuni.2014.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Vascular Endothelial Growth Factor Receptor-3 in Macrophages Restrains TLR4-NF-κB Signaling and Protects against Endotoxin Shock

Abstract: Toll-like receptors (TLRs) are critical in mediating innate immune responses against infections. However, uncontrolled TLR-triggered inflammation is associated with endotoxin shock. To better understand the homeostatic mechanisms induced by TLR4 signaling, we screened a group of key cytokines, chemokines, growth factors, and their receptors for bacteria- or LPS-induced expression. The surface vascular endothelial growth factor receptor-3 (VEGFR-3) and its ligand VEGF-C were upregulated in macrophages. VEGFR-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
126
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(143 citation statements)
references
References 52 publications
16
126
0
1
Order By: Relevance
“…Nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB) is another important signaling molecule that plays a key role in induction of pro-inflammatory cytokines and chemokines in microglia and macrophages [25,26]. We confirmed that CAPE (10 μM), an inhibitor of NF-κB [27], virtually abolished LPS-induced CXCL2 mRNA expression in BV-2 cells (Fig.…”
Section: Am80 Suppresses Nf-κb Signalingsupporting
confidence: 63%
“…Nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB) is another important signaling molecule that plays a key role in induction of pro-inflammatory cytokines and chemokines in microglia and macrophages [25,26]. We confirmed that CAPE (10 μM), an inhibitor of NF-κB [27], virtually abolished LPS-induced CXCL2 mRNA expression in BV-2 cells (Fig.…”
Section: Am80 Suppresses Nf-κb Signalingsupporting
confidence: 63%
“…Importantly, treatment with NEFAs also induced the over-expression of TLR2 and TLR4 in PMNs. These results obtained The intracellular signals downstream of TLR activation are propagated via the NF-κB pathway, which is an important redox-sensitive and proinflammatory transcription factor that plays a critical role in the regulation of a variety of genes involved in the inflammatory response [26]. The most classical NF-κB binding form is p65, which remains associated with the IκB family of inhibitory proteins in the cytoplasm before activation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Distinct phosphorylation of ERK by CLEC14A modulation upon stimula-deletion of Clec14a, increased vessel density following severe hemorrhaging appears more reliable. While the greater hemorrhagic potential of tumors in CLEC14A-KO mice is a possible cause of early death, we cannot exclude other potential causes, such as the inflammatory response to hemorrhagic shock or B16BL6 cell infiltration of the lungs (Figure 5Q), particularly since both VEGFR-3 and the CLEC14A paralog thrombomodulin regulate sepsis (52)(53)(54). Further immunological analysis of CLEC14A-deficient mice is required to determine the precise cause of early death.…”
Section: Discussionmentioning
confidence: 99%